A reliable quantitative method for determining CBD content and release from transdermal patches in Franz cells. Issue 8 (13th November 2022) - Yu, Liyun; Madsen, Frederikke Bahrt; Eriksen, Sofie Helvig; Andersen, Aaron J. C.; Skov, Anne Ladegaard
Abstract: Introduction: There are several cannabidiol (CBD) transdermal patches available on the market. However, none are FDA‐approved. Furthermore, not much evidence has been published about CBD release and skin permeation from such patches, so the effectiveness and reliability remain unclear. Objectives: We aimed to develop a method to determine the in vitro release and skin permeation of CBD from transdermal patches using Franz cell diffusion in combination with quantitative 1 H‐NMR (qNMR). Materials and Methods: The study was conducted on CBD patches with known CBD content and six different commercially available or market‐ready CBD patches using a Franz cell with a Strat‐M™ membrane and with samples taken directly from the transdermal patch for qNMR analysis. Results: The use of qNMR yielded an average recovery of 100% ± 7% when samples with known CBD content were tested. Results from the testing of six commercially available patches indicated that five out of six patches did not contain the CBD amount stated by the manufacturer according to a ± 10% variance margin, of which four patches were under‐labeled and one was over‐labeled. The release rate of patches was determined, and significant differences between the patches were shown. Maximum release of CBD was calculated to occur after 39 to 70 h. Conclusion: The established method was proven to be a reliable means of determining the quantity and release of CBD from transdermal patches and can be used to verify CBD content and release rate in transdermal patches. Abstract : We describe the use of Franz cell diffusion in combination with quantitative 1H‐NMR (qNMR) as a reliable method to determine the in vitro release and skin permeation of CBD from transdermal patches. Results from testing commercially available patches proved that 5 out of 6 patches did not contain the CBD amount stated by the manufacturer according to a ±10% variance margin wherein four patches were under‐labeled, and one was over‐labeled.